Undergraduate student experiences in remote lab courses during the COVID-19 pandemic - Victoria Borish; Alexandra Werth; Nidhal Sulaiman; Michael F. J. Fox; Jessica R. Hoehn; H. J. Lewandowski (Physical Review Physics Education Research, 2022)
The 2020–2021 academic year was a unique time for many instructors who had to adapt their courses to be conducted remotely due to the COVID-19 pandemic. This was especially challenging for physics lab courses, which usually emphasize hands-on experiments. Although many courses have now returned to in-person teaching, the possibility remains of future disasters necessitating similar remote courses. It is important to understand how undergraduate students experienced remote physics lab courses during the pandemic, including what aspects of the courses contributed to positive student outcomes. To investigate this, we surveyed over 5000 students from 24 different institutions, asking how the students engaged with their physics lab courses during the 2020–2021 academic year. Here, we describe the frequency with which the students performed various class activities, aspects of the course environment, challenges the students faced, aspects of the courses the students found enjoyable, and some student outcomes. We further study the impact of the course activities and course environment on four of the outcomes (self-reported learning of lab skills, self-reported learning of concepts, course enjoyment, and development of a sense of community). We find that students who were provided clear expectations, had enough time for their coursework, frequently worked in groups, and frequently had access to guidance from their instructors were more likely to report positive outcomes. This work demonstrates the importance of certain aspects of lab courses for several desirable outcomes in remote lab courses during a pandemic, with findings that may transfer to in-person or remote lab courses in the future.